Implementation of Project-Based Learning in Poetry Writing Learning in High School: A Qualitative Study of Literacy Processes and Experiences - Elvinda Harmonis Nur Munawaroh; Arisni Kholifatu Amalia Shofiani (Raja Zulkarnain Education Foundation, 2026)
This study aims to provide an in-depth description of the implementation of the Project Based Learning (PjBL) model in poetry writing instruction at the senior high school level, with a particular emphasis on the learning process and students’ literacy experiences. The research employed a descriptive qualitative approach and was conducted in a tenth-grade class at SMA Muhammadiyah 2 Mojoagung. The participants consisted of 30 students and one Indonesian language teacher. Data were collected through participatory observation during the project implementation, in-depth interviews with students and the teacher, and documentation of poetry drafts and final products. Data analysis was carried out through the stages of data reduction, data display, and interpretative conclusion drawing, using source triangulation techniques to ensure the credibility of the findings. The findings indicate that the implementation of PjBL fostered a more dialogic, collaborative, and reflective poetry writing environment. The poetry anthology project encouraged students to explore themes contextually, develop diction and imagery creatively, and engage in iterative revisions through peer feedback. These experiences contributed to the development of aesthetic awareness and a sense of responsibility toward the quality of their work. Moreover, collaborative interactions throughout the project strengthened students’ intrinsic motivation, empathy, and confidence in expressing personal experiences through poetic language. Therefore, the implementation of PjBL not only improved the quality of students’ poetry texts but also shaped meaningful and contextual literacy experiences in senior high school literature instruction.